Hemarthrosis of the knees following streptokinase therapy for acute myocardial infarction - Pimenta,Eduardo (2003)
A sixty-four-year-old male patient was studied who had acute coronary syndrome with ST segment elevation experienced bilateral hemarthrosis of the knees after administration of streptokinase and acetylsalicylic acid.